POLA PERGERAKAN PEMBELI TERHADAP TATA LETAK PEDAGANG KAKI LIMA DI PASAR SUMUR BATU JAKARTA PUSAT - Ni'mal Maulana Rizqi; Putra Fajar; Taslim Septia Prima; Dedi Hantono (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2020)
Sumur Batu Market is a growing market because of the existence of a modern market that is too far away. This market has many street vendors because of its busy location at night. The difference in sellers in the morning to evening and evening to night makes this market interesting to study. This happens because the traders who trade in the two different times and the movement of the people towards the two different times. The research to be carried out is carried out using personal observation, giving rise to documentation that is communicated in design and textually. The results of this study will bring up the results of the analysis of the zoning of traders that affect the pattern of buyer movement, both of which will provide its own advantages and disadvantages, especially in causing congestion on the road that causes congestion. Kata kunci: Activity, Market Circulation, Street Vendors, Informal Market.